The Effect of Solvent on The Extraction of Anthocyanin Pigment from Buni (Antidesma bunius (L) Spreng) - muryanto muryanto (Program Studi Teknik Kimia, Universitas Pamulang, 2022)
Buni fruit (Antidesma bunius (L) Spreng) contains vitamins, anthocyanins, flavonoids, and phenolic acids. Anthocyanins are a group of red to blue pigments widely distributed in plants. Anthocyanins in Buni are dyes that can be used as alternative natural dyes. In this research, anthocyanin will be extracted from Buni. The extraction process was carried out with various solvents, which are 10% citric acid, 70% ethanol, and distilled water for three days. The results showed the total levels of anthocyanins with 10% citric acid, 70% ethanol, and distilled water was 453.05 mg/L, 410.91 mg/L, and 361.64 mg/L. Citric acid is more optimal in extracting anthocyanins in Buni.